Endovascular Treatment of the Common Femoral Artery for Limb Ischemia. (November 2013) - Davies, Robert S. M.; Adair, William; Bolia, Amman; Fishwick, Guy; Sayers, Robert D.; McCarthy, Mark J.
Objective: To determine the short- and mid-term outcomes of percutaneous endovascular common femoral artery (CFA) revascularization (eCFR) of the CFA. Methods: A review of patients who underwent eCFR for limb ischemia between 2006 and 2012 was performed. Limb salvage, patient survival, survival free from reintervention, and survival free from amputation rates were determined. Median (range) follow-up was 28 (1-71) months. Results: In all, 115 patients underwent 121 eCFR for CFA occlusion (n = 13) or stenosis (n = 108); 109 (90%) were technically successful and 7 (6%) had significant perioperative complications; access site hematoma (n = 2) and thromboembolism (n = 5). Thirty-day mortality and amputation rates were 2.5% and 0.8%, respectively. The 1- and 3-year limb salvage rates were 97% and 97%, respectively. The 1- and 3-year survival free from reintervention rates were 77% and 57%, respectively. The 1- and 3-year survival free from amputation rates were 84% and 70%, respectively. Conclusion: These novel data demonstrate that eCFR is a durable treatment for patients with limb ischemia associated with CFA disease.